Gender and Indigenous Perspectives In English Courses - Kshetree, Arun Kumar; K. C, Kamala (Butwal Campus Journal, 2020)
This study presents the situation of inclusion of gender and indigenous perspectives in the M Ed English courses namely ‘Interdisciplinary Readings Part-1’ and ‘Readings in English’. It is basically a textual analysis of how gender roles are represented in the different texts of these courses and to whether there is the inclusion of indigenous knowledge in the texts to relate the previous knowledge of the readers with the new knowledge to be imparted. The researchers analyzed the texts in both courses and found that both courses were not able to respect gender balance in the matter of inclusion of female writers and female related issues though there are a significant number of texts with female names. Not only this, the inclusion of indigenous knowledge was also slightly neglected in both courses which may result in less interest of students. The researchers recommend including both perspectives properly in the courses of English so that the students enjoy learning new things linking them with what they have been practicing while reading the texts. The study will contribute to the syllabus designers, textbook writers, researchers and future teacher trainers for developing some insights related to these issues and help learners learn with pride and the feeling of ownership on gender issues and IK.